EFEKTIFITAS SLOW STROKE BACK MASSAGE (SSBM) DALAM MENURUNKAN SKALA NYERI KEPALA PASIEN HIPERTENSI DI RUMAH SAKIT MITRA SIAGA TEGAL - Purwani Istyawati; Dwi Budi Prastiani; Arif Rakhman (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Headache is a problem that is often felt by hypertensive patients. One of the non-pharmacological actions to reduce or treat headaches is the cutaneous slow stroke back massage (SSBM) stimulus. This massage is a comforting procedure that can relieve tension, relax the patient and improve circulation. The aim of the study was to determine the effect of SSBM on the pain scale in patients with essential hypertension. This research was conducted in the Inpatient Room of Mitra Siaga Tegal Hospital. This type of research is pre-experimental research design with one group pre test-post test, with accidental sampling technique. The statistical test used in this study is the t-paired test with the Shapiro Wilk normality test. The results showed that of the 18 respondents, the average value of the pain scale before being given SSBM was 5.83, while the average pain scale value after being given SSBM was 4.78. From the statistical test results obtained p = 0.000 <0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is an effect of giving SSBM on the headache scale of hypertensive patients. It is hoped that SSBM can be used as an SPO in pain management, especially headaches in hypertensive patients.